The political economy of external auditing in Malaysia 1957 - 1997 - Md. Ali, Azham (Penerbit Universiti Utara Malaysia, 1999)
This work investigates the role and contribution of external auditing as practiced in Malaysian society in the first 40 years since independence in 1957.It applies the political economic approach, which emphasises the social relations aspects of professional activity rather than economic forces alone.The political economic approach is applied by utilising an enlarged exogenous framework of processual change analysis.This particular interpretive framework views external auditing in Malaysia over the forty year period (1957-1997) as an open, dynamic social system comprising two pattern transformations.The study focuses specifically on the historical development of, and environment influences on the country’s audit practice and provides insights into the operational form of contemporary audit practice and the historical, social, economic and political determinants of that form.The writer extrapolates that in all probability, the future of auditing in Malaysia will continue to be constrained by unresolved problems; audit in Malaysia seems to be case of “the triumph of hope over experience”.